The Relationship Between Prolanis Participation and Blood Sugar Control Among Type 2 Diabetes Mellitus Patients at Puskesmas Sindangkerta - Sri Wahyuni; Moch Rezha Alfiqri; Sri Atun; Ryka Juaeriah (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Outpatient visits for Type 2 Diabetes Mellitus at Puskesmas Sindangkerta increased from 122 to 269 patients from February 2024 to January 2025, with Diabetes Mellitus service coverage reaching 186.69% of the estimated target. The Chronic Disease Management Program (Prolanis) was designed to improve the quality of life of patients with chronic diseases; however, empirical evidence on its association with blood sugar control in primary care settings in West Bandung Regency remains limited. This study aimed to analyze the relationship between Prolanis participation and blood sugar control among patients with Type 2 Diabetes Mellitus at Puskesmas Sindangkerta. A quantitative cross-sectional study was conducted using secondary data from the Prolanis register and medical records of patients with Type 2 Diabetes Mellitus for the period from February 2025 to January 2026. The sample consisted of 55 respondents selected through total sampling and analyzed using the Chi-square test (α = 0.05). The results showed that 37 respondents (67.3%) actively participated in Prolanis, and 39 respondents (70.9%) had controlled fasting blood sugar levels. The Chi-square test showed a significant association (p < 0.001), with an odds ratio (OR) of 10.057 (95% CI: 2.643–38.276) and a prevalence ratio (PR) of 2.22 (95% CI: 1.23–4.03). Active Prolanis participants had a 2.22-fold higher prevalence of controlled blood sugar levels than inactive participants (PR = 2.22; 95% CI: 1.23–4.03). Optimization of Prolanis through digital technology and continuous education is needed to support Diabetes Mellitus control in primary care settings. These findings provide an empirical basis for strengthening Prolanis through active monitoring and continuous education to improve blood sugar control among patients with Type 2 Diabetes Mellitus in primary care settings